Coverage of the Armenian Reform Issue in the Pages of “Horizon” - Karapetyan, Armen (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
At the beginning of the 20th century, the Armenian Question regained a strong urgency. This was caused by the Balkan crisis and the formation of a new international situation on the one hand, and by the further deterioration of the socio-economic situation of Western Armenians under Ottoman rule on the other. The Young Turks continued Sultan Hamid’s policy of the extermination of Armenians. In the autumn of 1912, European powers, primarily Russia, initiated negotiations with the Turkish authorities on the fundamental issue of implementing necessary reforms in the Western Armenian provinces. At the same time, the regions under the Turkish control further intensified the persecution of Armenians, aiming to depopulate the indigenous Armenian territories. All of this, in essence and depth, was reflected and illuminated in the pages of “Horizon”, an influential Armenian periodical published in Tiflis (Tbilisi) during 1912-1914. The material presented in "Horizon" is a truthful reflection of this complex and dramatic period of our history and serves as a true lesson and message for present and future generations.
Keywords: History